Research Trends of Suicidal Ideation in College Students: Causal Factors and Intervention - Abi Fa'izzarahman Prabawa; Nur Hidayah; Henny Indreswari; Adi Atmoko; M. Ramli; Eni Rindi Antika; Salwa Mahalle (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Suicidal ideation among university students has become a significant global mental health issue. Academic, social, and economic pressures increase students’ vulnerability to suicidal thoughts. Despite the growing number of studies, there is still no comprehensive bibliometric mapping that synthesizes research trends, risk factors, and interventions for the student population. This study aims to investigate the research trends related to suicidal ideation in students, identify contributing factors, and evaluate effective interventions. By employing a bibliometric approach and conducting a visual analysis of 382 documents from Scopus, the study uncovers common patterns and strategies that can be utilized to address this issue. The findings indicate that key risk factors include poor mental health, depression, and hopelessness. In contrast, social support, hope, and gratitude are emphasized as potential protective factors. Effective interventions identified in this study encompass enhancing social support, improving coping skills, ensuring access to mental health services, and implementing positive psychology-based therapies. This study has several limitations. The analysis is restricted to Scopus-indexed documents and depends on metadata quality, which may exclude relevant studies and introduce bias into the interpretation of results. Future research should incorporate additional databases, employ mixed-method designs, and test interventions grounded in a biopsychosocial–spiritual paradigm, including cybercounseling formats, to reduce suicidal desire and suicidal ideation among university students.